2019
DOI: 10.1039/c9ta09576d
|View full text |Cite
|
Sign up to set email alerts
|

Beyond 10% efficiency Cu2ZnSnS4 solar cells enabled by modifying the heterojunction interface chemistry

Abstract: ZnCdS buffer layers deposited from high concentration ammonia enable a less defective interface and over 10% efficiency Cu2ZnSnS4 solar cell.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 39 publications
2
52
0
Order By: Relevance
“…The CBO at CZTS/Zn 1-x Cd x S (ZnCdS) could be positive in the range of 0.1~0.3 eV while the Cd/(Zn + Cd) ratio is 0.62-0.75 [67]. Experimentally, the ZnCdS buffer layer based CZTS solar cells have been intensively studied by our group [40,46,48], yielding an efficiency beyond 10% with low V oc deficit to date [48]. By replacing CdS with the Zn 0.35 Cd 0.65 S buffer layer, a spike-like band alignment was achieved (Fig.…”
Section: Zn 1àx CD X S Buffer Layermentioning
confidence: 99%
See 2 more Smart Citations
“…The CBO at CZTS/Zn 1-x Cd x S (ZnCdS) could be positive in the range of 0.1~0.3 eV while the Cd/(Zn + Cd) ratio is 0.62-0.75 [67]. Experimentally, the ZnCdS buffer layer based CZTS solar cells have been intensively studied by our group [40,46,48], yielding an efficiency beyond 10% with low V oc deficit to date [48]. By replacing CdS with the Zn 0.35 Cd 0.65 S buffer layer, a spike-like band alignment was achieved (Fig.…”
Section: Zn 1àx CD X S Buffer Layermentioning
confidence: 99%
“…Additionally, a high concentration of ammonium hydroxide further improves the quality of ZnCdS due to reduced quantity of the Zn based secondary phases, thus significantly improving efficiency beyond 10% (Fig. 3c) [46,48]. However, the introduction of Zn into buffer usually leads to metastable behaviour of the electrical characteristics, which requires additional external treatment or carful modification of the heterojunction property.…”
Section: Zn 1àx CD X S Buffer Layermentioning
confidence: 99%
See 1 more Smart Citation
“…Fortunately, ZnS(e) is a large band gap compound and is expected to be rather benign if present in small amounts. It has even been reported that ZnS with similar crystalline structures to CZTS may passivate grain boundaries or heterojunction interface [81,95,96] by reducing strain and lowering recombination velocities at the grain interfaces. The tin compounds are unlikely to form because they are usually volatile [97] and will evaporate in most preparation conditions.…”
Section: Composition Variation and Phase Competitionmentioning
confidence: 99%
“…In the classical scheme, CZTS is basically integrated as an absorber layer in the rather complex SLG/Mo/p-CZTS/n-CdS/i-ZnO/ITO/Al multi-layered structure to fabricate solar cells, which have been shown to exhibit interesting PV performance [ 7 , 8 , 9 ]. However, the fabrication of this CZTS related multilayered architecture requires careful optimization of several laborious processing steps [ 10 , 11 , 12 ], namely: ( i ) post-sulfurization of the as-deposited CZTS layer, ( ii ) selective chemical treatment of CZTS surface (successive etching by KCN, NH 4 OH and HCl solutions), ( iii ) chemical deposition of the CdS buffer layer followed by soft thermal treatment, ( iv ) CZTS/CdS interface engineering, and ( v ) sputter-deposition of a ZnO/ITO top window contact layer.…”
Section: Introductionmentioning
confidence: 99%